The Brazilian Robotics Olympiad Extension Program - Curvelo, Carla Da Costa Fernandes; Pereira, Eduardo Bento; Pazelli, Tatiana F. P. A. T.; Aihara, Cintia Kimie (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
In an environment conducive to the dissemination of educational robotics and its results in the development of technical skills and soft skills of primary and secondary school students in Brazil, the organizing team of the Brazilian Robotics Olympiad, supported by RoboCup Brazil, developed an extension program to reach communities with low participation in competitions. Throughout Brazil, over the last 10 years, educational robotics courses have been developed and applied by university professors and state OBR representatives at schools, and for teachers and students for whom the possibility of working with technology, or even using it as a teaching and learning tool, was quite nonexistent. In recent years, centered on the creative learning approach, hands-on activities have been structured through instructional cards and challenges, which cover everything from electronic assembly to programming typical algorithms for solving RobocupJunior Rescue Line tasks. The program went through several phases, focusing on students, teacher training, the production of educational kits and, from now on, it seeks to develop course disseminators in schools and regions.